THERAPEUTIC EFFECT OF NYMPHAEA ALBA LINN. FLOWERS AGAINST ISONIAZID-INDUCED HEPATOTOXICITY: AN EXPERIMENTAL STUDY - Nasiruddin, Mohammad; Khan, Irfan Ahmad; Hasan Arif, Sayeedul (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was designed to evaluate the effect of ethanolic extract of Nymphaea alba (NAEE) Linn. flowers on liver marker enzymes, histology, and antioxidant tests against isoniazid (INH)-induced hepatotoxicity in rats. Methods: Wistar albino rats were treated with INH (50 mg/kg) for 28 days to induce hepatotoxicity. Silymarin (100 mg/kg) and NAEE Linn flowers in 200 mg/kg and 400 mg/kg doses, respectively, were used as standard and test drugs. Liver marker enzymes and histological examination of livers were performed to demonstrate the effect of NAEE against INH-induced hepatotoxicity. Catalase [CAT], glutathione, and malondialdehyde (MDA) levels were estimated to evaluate the antioxidant property of the NAEE extract. Results: The NAEE extract in 200 mg/kg and 400 mg/kg doses significantly decreased INH-induced elevation of liver marker enzymes as well as oxidative stress markers (CAT, glutathione, and MDA) in rats. Changes in biochemical parameters were supported by histological improvements of the liver. Conclusion: The NAEE Linn flowers in 200 mg/kg and 400 mg/kg doses showed a significant reversal of hepatic damage which was induced by INH in rats.